Efektivitas Model Discovery Learning Terhadap Kemampuan Komunikasi Matematis Siswa - Desi Ramadhani; Nurhanurawati Nurhanurawati; Santy Setiawati; Pentatito Gunowibowo (Lentera: Jurnal Ilmiah Kependidikan, 2026)
The purpose of this study was to determine the effect of discovery learning model on students' mathematical communication skills. All VIII grade students of SMP Negeri 6 Natar even semester of the 2023/2024 academic year as many as 209 students were used as the research population. The samples of this study were VIII E class consisting of 31 students and VIII C class consisting of 29 students selected by purposive sampling technique. The research design used was pre-test post-test control group design with class VIII E as the experimental class and VIII C as the control class. The data of this research is quantitative data obtained through student mathematical communication ability test. Hypothesis test analysis used in this study using t-test and proportion test. The results showed that the average gain data of mathematical communication ability of students who followed the discovery learning model was higher than the average gain data of mathematical communication ability of students who followed conventional learning and the proportion of students who had good categorized mathematical communication ability in the class that followed the discovery learning model was higher than the class that followed conventional learning. Thus, the discovery learning model is effective on students' mathematical communication skills.